Novel real-time optical imaging modalities for the detection of neoplastic lesions in urology: a systematic review - Brunckhorst,O; Ong,QJ; Elson,D; Mayer,E (Surgical Endoscopy, 2019)
Background Current optical diagnostic techniques for malignancies are limited in their diagnostic accuracy and lack theability to further characterise disease, leading to the rapidly increasing development of novel imaging methods within urology. This systematic review critically appraises the literature for novel imagining modalities, in the detection and staging ofurological cancer and assesses their effectiveness via their utility and accuracy.Methods A systematic literature search utilising MEDLINE, EMBASE and Cochrane Library Database was conducted from1970 to September 2018 by two independent reviewers. Studies were included if they assessed real-time imaging modalities not already approved in guidelines, in vivo and in humans. Outcome measures included diagnostic accuracy and utilityparameters, including feasibility and cost.Results Of 5475 articles identified from screening, a final 46 were included. Imaging modalities for bladder cancer includedoptical coherence tomography (OCT), confocal laser endomicroscopy, autofluorescence and spectroscopic techniques. OCTwas the most widely investigated, with 12 studies demonstrating improvements in overall diagnostic accuracy (sensitivity74.5–100% and specificity 60–98.5%). Upper urinary tract malignancy diagnosis was assessed using photodynamic diagnosis(PDD), narrow band imaging, optical coherence tomography and confocal laser endomicroscopy. Only PDD demonstratedconsistent improvements in overall diagnostic accuracy in five trials (sensitivity 94–96% and specificity 96.6–100%). Limitedevidence for optical coherence tomography in percutaneous renal biopsy was identified, with anecdotal evidence for anymodality in penile cancer.Conclusions Evidence supporting the efficacy for identified novel imaging modalities remains limited at present. However,OCT for bladder cancer and PDD in upper tract malignancy demonstrate the best potential for improvement in overall diagnostic accuracy. OCT may addit